THE VALUE OF AL-QURAN STUDY IN DEVELOPING SOCIETIES A CASE STUDY OF MASJID WAKAF BHARU, KELANTAN AL-QUR'AN AND TAJWID COURSE - Ab Rahman , Siti Maziah; Mohd Zaki, Adeeba Najihah; Ab Rahman, Hasnuddin (Journal of Islamic, Social, Economics and Development, 2024)
The ability to read the Qur’an is a basic skill that every Muslim must possess. Remembering the Qur’an as the holy book of Muslims as well as a life guide towards the path of truth. This ability includes accuracy in reciting the Qur’an by the correct tajwid and makhraj. This paper discusses the importance of studying the Qur’an and its knowledge in growing Islamic development. To obtain data and research material, a case study was conducted in the Al-Qur’an, & Tajwid Study Class at the Masjid Wakaf Bharu, Kelantan. It looks at the teaching methods and techniques applied in lectures, as well as their achievements and effectiveness in giving awareness to the public in appreciating the basic values of the teachings of the Qur’an to develop themselves and the people. The research method is observation, as well as interviews and questionnaires with the teaching staff and the participants to see their level of understanding about the significance of this study class in increasing religious awareness and growing identity and community. In general, the organized lectures have succeeded in instilling religious values and inputs that are effective in polishing the participants' understanding of the knowledge of the Qur’an. In this regard, improvement efforts should continue by emphasizing tajdid aspects within the framework of the syllabus and the learning process. This is highlighted in this paper by proposing several reforms to improve the standard and quality of studies with reconstruction and innovation in teaching as well as the integration of the curriculum with the humanities and current thinking. In conclusion, with the clear consequences of the effectiveness of organizing al-Qur’an study classes for the public, this initiative should be developed more aggressively and broadly to produce a generation of al-Qur’an literate people who can make significant contributions instrumental in building growth and development.